The Book as Event: On the Russian Translation of Film Art by D. Bordwell, K. Thompson, and J. Smith - Diane Nemec Ignashev; Polina Yu. Rybina (Литература двух Америк, 2025)
First published in 1979 and originally based on Bordwell’s film studies lectures at the University of Wisconsin, Madison, over the last forty-five years in its continuing reissues and translations into other languages, Film Art: An Introduction has come to represent the gold standard for humanistic introductory film analysis pedagogy in the United States and beyond. Recently the first Russian edition of the reputed textbook (its 12th edition) was published by Bombora (2024). The present publication offers an authorized transcript in Russian translation of an interview with renowned film scholars Kristin Thompson and Jeff Smith (University of Wisconsin, Madison), co-authors with David Bordwell (1947–1924) of Film Art: An Introduction. The interview was conducted in September 2024 by film and Russian literature scholar Diane Nemec Ignashev (Carleton College, Minnesota) to mark publication in Russian of the book Film Art. In the interview Thompson and Smith address the influence of Russian Formalism on Bordwell’s approach to film analysis, principles of film studies pedagogy, textbook writing and responses to instructors’ criticisms and needs, professional development, the future of media studies, and the potential impact of artificial intelligence technologies on the film industry. In their article Polina Rybina and Diane Nemec Ignashev outline the larger context of the interview and provide an overview of David Bordwell’s many contributions to film studies.